The effect of lower limb passive movement on lung function - S. Narain; J. Lin; T. Puckree (AOSIS, 2001)
This study examined the effects of ankle passive movement on lung function in healthy adults. A pre-test post-test experimental design was used. Passive plantar and dorsiflexion of the ankle were performed at 60 repetitions per minute on 60 healthy subjects in the supine position. Lung function at rest was compared to that during passive movements. The results indicated that all measured parameters including the breathing frequency, tidal volume, minute ventilation, oxygen consumption and carbon dioxide output, increased significantly during passive movements as compared to those at rest. The authors conclude that passive movements elicit a significant ventilatory increase in healthy human subjects. The effect of passive movements in the treatment of unconscious or diseased individuals should be investigated.